The cyclic and linear sweep voltammetry of regular and random arrays of microdisc electrodes: Theory - Davies, T; Compton, R (2005)
Microdisc electrode arrays are popular tools in electroanalytical chemistry. In linear sweep and cyclic voltammetry experiments, for optimum performance the individual discs in the array must have a centre-to-centre separation large enough to avoid diffusion zone overlap (which is also known as "shielding"), but not too large as to result in a waste of surface area. Using a 2-dimensional simulation method, this work examines in detail the currently accepted guidelines on centre-to-centre separation and identifies the key factors involved in the voltammetry of both regular and random arrays of microdisc (and nanodisc) electrodes. © 2005 Elsevier B.V. All rights reserved.